Cryptorchidism in the rat: a possible model to study testicular dysgenesis syndrome (TDS) - Cardoso, Ana Paula Ferragut [UNESP] (2015)
Cryptorchidism is a congenital defect affecting 2-4% of newborn boys, and is a major risk factor for infertility and testicular germ cell tumors (TGCT). The surgery that reallocates the testis into the scrotum, ochiopexy, should be performed between 6-12 months of age in order to allow normal fertility and reduce the risk of malignancy. Poor semen quality, undescended testis, hypospadias and TGCT are elements that, isolated or combined, compose the so-called Testicular Dysgenesis Syndrome (TDS). The present study aimed to characterize the testicular changes induced by a cryptorchidism and orchiopexy experimental model in the rat with the eventual purpose of better understanding TDS. Improved mechanical methods of abdominal cryptorchidism induction and a variation in the orchiopexy installation by anchoring the testes, and not the cauda epididymis, into the internal surface of the scrotal wall and gently pulling them down to the scrotum, are presented. To accomplish that, Sprague-Dawley male rats were surgically submitted to cryptorchidism by anchoring the testicular albuginea to the abdominal wall - the critical step of the present method - at 3 weeks of age; some of them were euthanized 3, 6 or 11 weeks after this surgery in order to register the morphological progression of cryptorchidism-induced testicular alterations. Other cryptorchidic animals were submitted to orchiopexy 3, 5 or 9 weeks after cryptorchidism; these animals were euthanized 3 or 8 weeks after orchiopexy. Sham operated animals underwent to cryptorchidism and orchiopexy at the same times as the surgical groups. At least 10 and 5 animals were used in surgical and sham groups, respectively, at the respective euthanasia moments. Cryptorchidic testis showed decreased weights, germ cell loss, spermatogenesis disruption, apoptosis and eventually some tubules with a Sertoli cells-only pattern, findings already described with other mechanical methods used to induce ...